Effects of foliar iron oxide nanoparticles (Fe3O4) application on photosynthetic parameters, distribution of mineral elements, magnetic behaviour, and photosynthetic genes in tomato (Solanum lycopersicum var. cerasiforme) plants - Tombuloglu, Guzin (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.